Service design for children and young people with common mental health problems: literature review, service mapping and collective case study - Steven Pryjmachuk; Susan Kirk; Claire Fraser; Nicola Evans; Rhiannon Lane; Liz Neill; Elizabeth Camacho; Peter Bower; Penny Bee; Tim McDougall (NIHR Journals Library, 2024)
Background The mental health of children/young people is a growing concern internationally. Numerous reports and reviews have consistently described United Kingdom children's mental health services as fragmented, variable, inaccessible and lacking an evidence base. Little is known about the effectiveness of, and implementation complexities associated with, service models for children/young people experiencing 'common' mental health problems like anxiety, depression, attention deficit hyperactivity disorder and self-harm. Aim To develop a model for high-quality service design for children/young people experiencing common mental health problems by identifying available services, barriers and enablers to access, and the effectiveness, cost effectiveness and acceptability of such services. Design Evidence syntheses with primary research, using a sequential, mixed-methods design. Inter-related scoping and integrative reviews were conducted alongside a map of relevant services across England and Wales, followed by a collective case study of English and Welsh services. Setting Global (systematic reviews); England and Wales (service map; case study). Data sources Literature reviews: relevant bibliographic databases and grey literature. Service map: online survey and offline desk research. Case study: 108 participants (41 children/young people, 26 parents, 41 staff) across nine case study sites. Methods A single literature search informed both reviews. The service map was obtained from an online survey and internet searches. Case study sites were sampled from the service map; because of coronavirus disease 2019, case study data were collected remotely. 'Young co-researchers' assisted with case study data collection. The integrative review and case study data were synthesised using the 'weaving' approach of 'integration through narrative'. Results A service model typology was derived from the scoping review. The integrative review found effectiveness evidence for collaborative care, outreach approaches, brief intervention services and the 'availability, responsiveness and continuity' framework. There was cost-effectiveness evidence only for collaborative care. No service model appeared to be more acceptable than others. The service map identified 154 English and Welsh services. Three themes emerged from the case study data: 'pathways to support'; 'service engagement'; and 'learning and understanding'. The integrative review and case study data were synthesised into a coproduced model of high-quality service provision for children/young people experiencing common mental health problems. Limitations Defining 'service model' was a challenge. Some service initiatives were too new to have filtered through into the literature or service map. Coronavirus disease 2019 brought about a surge in remote/digital services which were under-represented in the literature. A dearth of relevant studies meant few cost-effectiveness conclusions could be drawn. Conclusions There was no strong evidence to suggest any existing service model was better than another. Instead, we developed a coproduced, evidence-based model that incorporates the fundamental components necessary for high-quality children's mental health services and which has utility for policy, practice and research. Future work Future work should focus on: the potential of our model to assist in designing, delivering and auditing children's mental health services; reasons for non-engagement in services; the cost effectiveness of different approaches in children's mental health; the advantages/disadvantages of digital/remote platforms in delivering services; understanding how and what the statutory sector might learn from the non-statutory sector regarding choice, personalisation and flexibility. Study registration This study is registered as PROSPERO CRD42018106219. Funding This award was funded by the National Institute for Health and Care Research (NIHR) Health and Social Care Delivery Research programme (NIHR award ref: 17/09/08) and is published in full in Health and Social Care Delivery Research; Vol. 12, No. 13. See the NIHR Funding and Awards website for further award information. Plain language summary In this research study, we explored services for children and young people with 'common' mental health problems like depression, anxiety and self-harm. We aimed to find out what services exist, how children/young people and families find out about and access these services, what the services actually do, whether they are helpful and whether they offer value for money. We looked at the international literature (reports and research papers) to identify different approaches to providing support, and to find out whether certain approaches worked better than others and whether children/young people and families preferred some approaches over others. The literature provided very little information about the value for money of services. We also carried out a survey and used the internet to identify 154 relevant services in England and Wales. To explore services in more detail, and hear directly from those using them, we planned to visit 9 of the 154 services to interview children/young people, parents and staff. Unfortunately, coronavirus disease 2019 stopped us directly visiting the nine services and so we conducted phone and video interviews instead. We still managed to speak to, and hear the experiences of, more than 100 people (including children/young people and parents). We combined information from the literature with information from the interviews to create an evidence-based 'model' of what services should look like. This model considers some basic things like how quickly children/young people could access a service, what information was available, the importance of confidentiality and whether staff make the service fit with the child/young person's needs and interests. It also considers whether the service helps children/young people learn skills to manage their mental health and whether staff at a service work well together. We hope our model will help existing and new services improve what they offer to children/young people and families. Scientific summary Background This study is a response to a National Institute for Health and Care Research (NIHR) commissioning call on research to improve services for children and young people (CYP) with common mental health problems (CMHPs). The mental health of CYP has been a growing public health concern both nationally and internationally. Estimates from 2021, covering the height of the coronavirus disease 2019 (COVID-19) pandemic, suggest that around one in six CYP in England may be experiencing significant mental health difficulties, including the likes of anxiety, depression, self-harm and behavioural difficulties. The tiers model has dominated UK service provision for at least two decades. However, it has become increasingly clear that this model has not met the needs of most CYP experiencing mental health problems. Numerous reports and reviews have consistently described UK children's mental health services as fragmented, unco-ordinated, variable, inaccessible and lacking an evidence base. While there have been recent attempts to transform services using initiatives such as Choice and Partnership Approach (CAPA), Children and Young People-Improving Access to Psychological Therapies (CYP-IAPT) (a CYP's version of adult IAPT) and THRIVE, little is known about the effectiveness of these initiatives nor the effectiveness of children's mental health service models in general. Moreover, the disparate factors associated with accessing and navigating services for CYP experiencing CMHPs have not been synthesised into a coherent model of effective and acceptable service provision. Aims and objectives The study's overarching aim was to develop a model of high-quality service design for CYP experiencing CMHPs by identifying available services, the barriers and enablers to access, and the effectiveness (including cost effectiveness) and acceptability of, those services. Six objectives were derived from this aim: Systematically search, appraise and synthesise the international literature on services for this population group in order to (1) build evidence of the effectiveness and acceptability of current service provision and (2) assist with objective 2.